2018
DOI: 10.1002/oby.22214
|View full text |Cite
|
Sign up to set email alerts
|

Does Love Really Make Mothers Blind? A Large Transcontinental Study on Mothers' Awareness About Their Children's Weight

Abstract: Most children with overweight and/or obesity were perceived as normal weight by their mothers. Such lack of concern regarding a severe disease might interfere with the effectiveness of prevention programs. Considering the contextual factors that frame the etiological causes of a disease may help in finding effective and enduring solutions to target childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Our cross-sectional analyses confirmed a strong positive association between the child’s current weight status and parental concern, suggesting parents of children with a BMI in the overweight and obese range are more likely than other parents to be concerned about their child’s future overweight risk. This is important, given the suggestion that appropriate parental concern is vital for effective parental engagement with obesity intervention programmes7 and positive behaviour change 6. Further research is needed to determine whether parental concern is associated with healthier weight trajectories, as well as to understand how feedback given to parents about their child’s weight status from the NCMP can be appropriately and accurately conveyed to parents from different ethnic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cross-sectional analyses confirmed a strong positive association between the child’s current weight status and parental concern, suggesting parents of children with a BMI in the overweight and obese range are more likely than other parents to be concerned about their child’s future overweight risk. This is important, given the suggestion that appropriate parental concern is vital for effective parental engagement with obesity intervention programmes7 and positive behaviour change 6. Further research is needed to determine whether parental concern is associated with healthier weight trajectories, as well as to understand how feedback given to parents about their child’s weight status from the NCMP can be appropriately and accurately conveyed to parents from different ethnic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that parental concern about their child’s current weight status6 and about their child becoming overweight in the future7 may be meaningful predictors of willingness to engage in behaviour change.…”
Section: Introductionmentioning
confidence: 99%
“…Those parents who are in no position to perceive the real weight of their children (i.e., they consider their child of average weight or even underweight) have little or no chance of taking the appropriate steps to change the unhealthy lifestyle of their children and prevent obesity. [ 12 13 ] In Europe, America, Asia, and Australia it has been documented that most overweight or obese children are regarded by their parents as slimmer than they are in reality. [ 12 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 13 ] In Europe, America, Asia, and Australia it has been documented that most overweight or obese children are regarded by their parents as slimmer than they are in reality. [ 12 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…During childhood, and according to the traditional gender role, the mother is the main caregiver (5), the reason why she is in a unique position to exert an influence on her child's lifestyle behaviors. However, the literature has documented that the mothers of overweight-obese children have an inadequate perception of the child's weight: they underestimate it (6)(7)(8)(9)(10). Therefore, they could be less willing to motivate them to participate in healthy behaviors and less likely to resort to health services (6).…”
Section: Introductionmentioning
confidence: 99%